2022
DOI: 10.47067/ramss.v5i3.252
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Afghan Refugee Influx on Labor Market Outcomes in Pakistan

Abstract: The study gauges the impact of refugee influx on the labor market in Pakistan. The impact of Afghan refugees is analyzed using three indicators of labor market namely, unemployment, formal employment and informal employment from years 1979 to 2022. For the purpose of analysis, ADF and PP tests are applied first for examining unit root problem. Variables are found having mixed order of integration so ARDL bound test for co-integration is used to derive long run and short run relationship between labor market in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…From the literature and discussion cited above, it is concluded that the relationship between economic growth and terms of trade is not linear. Nabine (2009) mentioned that it is essential that theoretical growth has received attention between trade policies and economic development (Javaid et al, 2022). Afghan refugees have a positive and significant long-run relationship with the Pakistan labor market by applying the ARDL bound test from 1979 to 2020 (Durkin, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the literature and discussion cited above, it is concluded that the relationship between economic growth and terms of trade is not linear. Nabine (2009) mentioned that it is essential that theoretical growth has received attention between trade policies and economic development (Javaid et al, 2022). Afghan refugees have a positive and significant long-run relationship with the Pakistan labor market by applying the ARDL bound test from 1979 to 2020 (Durkin, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%